2016
DOI: 10.1007/s00249-016-1152-z
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of tumour xenografts with an antibody targeting the potassium channel Kv10.1

Abstract: The Kv10.1 (Eag1) voltage-gated potassium channel represents a promising molecular target for novel cancer therapies or diagnostic purposes. Physiologically, it is only expressed in the brain, but it was found overexpressed in more than 70 % of tumours of diverse origin. Furthermore, as a plasma membrane protein, it is easily accessible to extracellular interventions. In this study we analysed the feasibility of the anti-Kv10.1 monoclonal antibody mAb62 to target tumour cells in vitro and in vivo and to delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…[28] More often analogues of endogenous ligands are used for the pursuit of improved pharmacokinetics and safety profile, simplified synthesis, conjugation process, and so forth (Figure 4a). For instance, based on endogenous -(2,9)-oligosialic acid sugar epitope and mannose, -(2,9)-trisialic acid and 2amino-2-deoxymannose were conjugated with cyanine fluorophores for targeted imaging of sia-binding immunoglobulinlike lectins on PC-12 cells (16) and mannose receptors on tumorassociated macrophages (17), respectively. [29] And it is more common in the case of endogeneous peptide ligands, wherein the so-called peptidomimetic strategy is adopted to design warheads that mimic the receptor-ligand interaction.…”
Section: Probes For Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] More often analogues of endogenous ligands are used for the pursuit of improved pharmacokinetics and safety profile, simplified synthesis, conjugation process, and so forth (Figure 4a). For instance, based on endogenous -(2,9)-oligosialic acid sugar epitope and mannose, -(2,9)-trisialic acid and 2amino-2-deoxymannose were conjugated with cyanine fluorophores for targeted imaging of sia-binding immunoglobulinlike lectins on PC-12 cells (16) and mannose receptors on tumorassociated macrophages (17), respectively. [29] And it is more common in the case of endogeneous peptide ligands, wherein the so-called peptidomimetic strategy is adopted to design warheads that mimic the receptor-ligand interaction.…”
Section: Probes For Receptorsmentioning
confidence: 99%
“…Combinatorial chemistry libraries, especially innovative dynamic combinatorial library and DNA-encoded library, commonly involved in target-based drug discovery are also applicable to ligand discovery as their underlying principles are interchangeable. [34] Additionally, biological screening platforms that rely on miscellaneous display systems, either cellular or acellular, to construct genetic mutant libraries www.advancedsciencenews.com www.advhealthmat.de (13)(14)(15) or its biomimetics (16)(17)(18)(19)(20) as targeting warheads. b) 3D image of mouse administered with conjugate 15 using fluorescence imaging tomography (FLIT) mode and confirmation of tumor cells in the primary tumor and four metastatic lymph nodes through H&E staining or cytokeratin immunostaining.…”
Section: Probes For Receptorsmentioning
confidence: 99%
“…The full-length IgG from which scFv62 was derived has been used for in vivo imaging of tumor xenografts, providing further evidence of the utility of these antibodies in targeted cancer therapy. 199 K v 11.1B K V 11.1 (also known as hERG1) channels are often overexpressed in human cancers, but targeting them risks cardiotoxicity. CD-160,130 is a small molecule compound that blocks K v 11.1 channels with a higher efficacy for the K v 11.1 isoform B, 121 and shows anti-tumor effects without the cardiovascular toxicity induced by K v 11.1 blockade.…”
Section: P2x7mentioning
confidence: 99%
“…In such a way, an anti-Kv10.1 mAb (mAb62) was used to target tumor cells in vitro using the human breast MDA-MB-435S cell line and in vivo on tumor models of nude mice (Napp et al, 2016). The authors demonstrated the specific binding and accumulation of the mAb62 in the tumors in vivo for at least 1 week due to the labeling with Cy5.5 fluorophore.…”
Section: Potassium Channelsmentioning
confidence: 99%